Nurses' early and ongoing encounters with the dying and the dead: a scoping review of the international literature. (2nd August 2020) - Jones, Kerry; Draper, Jan; Davies, Alison
Abstract : Background: End-of-life care is high on policy and political agendas in the UK and internationally. Nurses are at the forefront of this, caring for dying patients, 'managing' the dead body, and dealing with the corporeal, emotional and relational dimensions of death. Little is known about nurses' prior or early professional experiences of and reactions to death, dying and the corpse and how these might influence practice. Aims: To appraise the international literature on nurses' early experiences of death, dying and the dead body, to better understand how these might influence subsequent practice, and how this might inform our teaching of death, dying and last offices. Methods: A scoping review was undertaken of peer-reviewed publications between, 2000 and 2019, which included nurses working in hospital, care homes and the community. Medline, PubMed, PsychINFO and CINAHL databases were searched and 23 papers meeting the inclusion criteria were read. Arksey and O'Malley's (2005) five-stage approach was adopted to scope the relevant international literature, using where relevant the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement. Selected papers were independently reviewed and subjected to thematic analysis, leading to the generation of five overarching themes. Results: The five themes were: different philosophies of care; relationships; knowledge; impact of death; and giving care. The studies came from diverse geographical locations across different settings and were primarily qualitative in design. Conclusions: Students and registered nurses are impacted both positively and negatively by their early encounters with death and dying. Good communication with patients, families and between professionals, understanding of what constitutes a 'good' death, and high-quality mentorship and support were of particular importance.